Uji Daya Antiinflamasi Ekstrak Etanol Daun Mangkokan (Nothopanax Scutellarium Merr.) pada Mencit Yang Diinduksi Karagenin - Tia Intan Pradita; Sri Rejeki (Indonesian Journal on Medical Science, 2022)
Mangkokan leaves (Nothopanax scutellarium Merr.) contain flavonoids, alkaloids, saponins, and polyphenols which are used to treat wounds, antibacterial, anti-inflammatory, and antioxidants. This study aims to determine the ethanol extract of mangkokan leaves has anti-inflammatory power in mice induced by carrageenan and to determine the effective dose of mangkokan leaf ethanol extract which provides anti-inflammatory power comparable to the positive control. This type of research is experimental. Mangkokan leaves were extracted by maceration method using 70% ethanol solvent. The test animals used were 25 mice and divided into 5 groups. All groups were induced with carrageenan. Group I was given positive control (na diclofenac), group II was given negative control (coconut oil), and groups III, IV, V were given ethanol extract of mangkokan leaves each with a dose of 100 mg / kg, 200 mg / kg, 400 mg / kgBB. The results of measuring the length of edema every 30 minutes for 6 hours were analyzed with the help of SPSS version 22.0 for windows. Results% DAI of the ethanol extract of mangkokan leaves with a dose of 400 mg was 58.88%, a dose of 200 mg was 50.49%, a dose of 100 mg was 43.67%, and a positive control was 66.71%. The conclusion of this study is that the ethanol extract of mangkokan leavesÂ  anti-inflammatory activity in mice which is comparable to the positive control with a dose of 400 mg.The ethanol extract of mangkokan leaves has the potential to be anti-inflammatory.